Poverty outreach and BRAC’s microfinance interventions: programme impact and sustainability - Halder, Shantana R (BRAC Research and Evaluation Division (RED), 2020)
This paper is based on the experience and evolution of a large microfinance provider BRAC - which is working in Bangladesh. The paper stresses that poverty is not homogeneous, but is manifested in different ways and in different contexts. It considers BRAC's response to this broader understanding of poverty in Bangladesh, referring particularly to the ways in which specific programmes were tailored and adapted to embrace new information about client needs and behaviour. The study goes on to discuss impact assessment studies conducted on BRAC's main poverty alleviation programme in rural areas - Rural Development Programme - that provided significant data to substantiate BRAC's positive effect on poverty alleviation, as well as providing information that led to subsequent programmatic shills in emphasis.